CRISPR Technology in Gene-Editing-Based Detection and Treatment of SARS-CoV-2 - Shademan, Behrouz; Nourazarian, Alireza; Hajazimian, Saba; Isazadeh, Alireza; Biray Avci, Cigir; Oskouee, Mahin Ahangar (Frontiers in Molecular Biosciences, 2022)
The outbreak and rapid spread of coronavirus disease caused by coronavirus-2 (COVID -19), which caused severe acute respiratory syndrome (SARS-CoV-2) and started in Wuhan, has become a global problem because of the high rate of human-to-human transmission and severe respiratory infections. Because of the high prevalence of SARS-CoV-2, which threatens many people worldwide, rapid diagnosis and simple treatment are needed. Therefore, early diagnosis and application of treatment strategies are critical for the effective control of this disease. Genome editing is an approach to altering the genome, which depends on nucleic acid (DNA) by artificially altering genetic information and inducing irreversible changes in the function of the altered gene. Clustered, regularly interspaced short palindromic repeats (CRISPR/Cas) could be a practical and straightforward approach to this disease. The CRISPR/Cas system contains the Cas protein, controlled by a small RNA molecule to create a double-stranded DNA gap. According to the researchers, CRISPR/Cas has also been studied for its potential use in diagnosing and treating SARS-CoV-2 infections. Another aspect of this research addressed potential future problems with CRISPR/Cas applications.